Antennae. - Pelosi, Giuseppe; Selleri, Stefano; Valotti, Barbara
The main purpose of this short communication is to report the introduction of the word antenna in the scientific and technical terminology, going back in time from ancient times up to Marconi's first communications.
Keywords: Terminology; Antennas; Etymology